2007
DOI: 10.1080/14616730701711581
|View full text |Cite
|
Sign up to set email alerts
|

A sibling adoption study of adult attachment: The influence of shared environment on attachment states of mind

Abstract: This study extends existing research investigating sibling concordance on attachment by examining concordance for adult attachment in a sample of 126 genetically unrelated sibling pairs. The Adult Attachment Interview (George, Kaplan, & Main, 1985;Main, Goldwyn, & Hesse, 2003) was used to assess states of mind with regard to attachment. The average age of the participants was 39 years old. The distribution of attachment classifications was independent of adoptive status. Attachment concordance rates were unass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 56 publications
1
10
0
1
Order By: Relevance
“…Van Ijzendoorn, Moran, Belsky, et al (2000) found around 60% concordance for siblings' attachment behaviour, and other studies obtained similar results with dizygotic twins (e.g. O'Connor & Croft, 2001) and even with adults adopted in infancy or childhood (Caspers, Yucuis, Troutman, Arndt, & Langbehn, 2007). This result excludes the genetic effects present with monozygotic twins but absent from adopted siblings, suggesting the influence of environment on the development of attachment.…”
Section: Concordance Of Attachment Between Siblingssupporting
confidence: 61%
“…Van Ijzendoorn, Moran, Belsky, et al (2000) found around 60% concordance for siblings' attachment behaviour, and other studies obtained similar results with dizygotic twins (e.g. O'Connor & Croft, 2001) and even with adults adopted in infancy or childhood (Caspers, Yucuis, Troutman, Arndt, & Langbehn, 2007). This result excludes the genetic effects present with monozygotic twins but absent from adopted siblings, suggesting the influence of environment on the development of attachment.…”
Section: Concordance Of Attachment Between Siblingssupporting
confidence: 61%
“…Twin and adoption studies [21,22] using the AAI have robustly suggested that the AAI assesses the unique meaning the adult has given to his or her attachment history and further, that this meaning is likely to reflect the environment (shared and nonshared) within families. A rather different, more genetic-driven set of findings has been suggested by questionnaire or self-report measures of adult romantic attachment styles operationalized on the dimensions of avoidance or anxiety, in which the suggestion emerges that these attachment constructs overlap with the Big Five personality traits in ways that point to shared genetic influences [20].…”
Section: Relevance Of Attachment-based Research Tools In Studies Of Pmentioning
confidence: 99%
“…In the case of the former self-report measure, yielding scores for avoidance and anxiety, recent evidence suggests that they are in part heritable [20]. In contrast, environmental-not genetic-effects are highlighted in sibling studies [21] and adoption studies [22] relying on the AAI. Furthermore, robust meta-analytic evidence from 10,000 respondents linking AAI responses to mental health outcomes [23•] underscores the value of the AAI as an indicator of psychotherapeutic treatment progress and outcome [3, 24•].…”
Section: Introductionmentioning
confidence: 99%
“…Validity evidence is strong for conceiving of AAI security/insecurity as being linked not to one's genetic makeup but to shared (and nonshared or relationship-specific) environmental influences (Caspers, Yucuis, Troutman, Arndt, & Langbehn, 2007;. Powerful associations across generations between AAI responses of parents and infant patterns of attachment have attracted much attention, from Main et al's (1985) report through and beyond the first metaanalytic report on 854 parentÁchild relationships studied (van IJzendoorn, 1995) showing a large effect size (Cohen's d01.06) for AAI security/ insecurity predicting infantÁparent security/insecurity.…”
Section: Divergent Traditions Of Attachment Research In Developmentalmentioning
confidence: 92%